Trauma, stigma, and autism : developing resilience and loosening the grip of shame - Gates, Gordon S. (Gordon Stanley Peter), 1966- (Jessica Kingsley Publishers, 2019)
This book explores how stigma can cause trauma, providing guidance on how marginalised people can develop resilience to manage and heal from traumatic stigma. Gordon Gates draws on his experience as a crisis counsellor, philosophical research, and his lived experience of stigma, trauma and autism.